Science in formerly socialist countries: Asset or liability within new societal conditions? - Werner Meske (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Knowledge and learning are seen as key success factors for international competitiveness and economic growth in contemporary societies and have been placed at the top of the policy agenda in many countries. But actual developments in former socialist countries of Europe and Asia have totally run counter to such aims in the last decade. Science and technology (S&T) in the transformation countries have undergone major changes on all planes, as simultaneously institutional corrections within the S&T system have taken place and the systemic changeover in the political and economic fields has also effected major changes to the size, structure and content of the domestic demand for scientific results and services, and in addition to that, the international opening-up to high-tech imports and other forms of technology transfer has further minimised the need for domestic R&D. Despite big shifts in the spectrum of scientific activities, only partial devaluation of knowledge and skills has taken place, and experience in research has actually proved invaluable in coping with new tasks inside and outside of scientific institutes. But, the inherited institutional preconditions in science and research, along with individual knowledge and levels of educational attainment are not assets and advantages in and of themselves. They must constantly be seen in relation to the overall societal framework. Indeed, the problem seems to be one of how to employ, change and utilise the personnel and other capacities inherited from the socialist era, with the abilities, skills, experiences etc. that it has, in such a way that it is able to meet the new demands, to cope with the challenges and to act as an asset under conditions of globalisation. – – Wissen und Lernen werden als Erfolgsfaktoren für internationale Wettbewerbsfähigkeit und Wirtschaftswachstum in modernen Gesellschaften angesehen und nehmen einen Spitzenplatz in der Politik vieler Länder ein. Die tatsächliche Entwicklung in den früher sozialistischen Ländern Europas und Asiens ist jedoch im letzten Jahrzehnt völlig entgegengesetzt verlaufen. Wissenschaft und Technik (W&T) der Transformationsländer haben vielfältige Veränderungen erfahren, da neben institutionellen Korrekturen in W&T der Systemwandel in Politik und Wirtschaft auch Umfang, Struktur und Inhalt der Nachfrage nach wissenschaftlichen Ergebnissen und Leistungen wesentlich verändert hat. Zusätzlich hat die internationale Öffnung für high-tech Importe und Technologietransfer den Bedarf an einheimischer FuE weiter schrumpfen lassen. Trotz der erheblichen Verschiebungen im Spektrum wissenschaftlicher Aktivitäten sind Kenntnisse und Fähigkeiten nur teilweise entwertet worden; Forschungserfahrungen waren vielmehr vorteilhaft für die Bewältigung neuer Aufgaben innerhalb und außerhalb der Wissenschaft. Jedoch sind vorhandene Institutionen in Wissenschaft und Forschung sowie individuelles Können und Qualifikationen nicht an und für sich günstige Voraussetzungen und von Vorteil. Sie müssen immer in das jeweilige gesellschaftliche Umfeld eingeordnet werden. In Wirklichkeit besteht das Problem also darin, die aus der sozialistischen Ära übernommenen Kapazitäten und insbesondere das Personal mit seinen Fähigkeiten, Fertigkeiten und Erfahrungen so einzusetzen, anzupassen und zu nutzen, dass es den neuen Anforderungen entspricht, sich den Herausforderungen stellt und so tatsächlich als ein Aktivposten unter den Bedingungen der Globalisierung wirksam wird.
Keywords: 300; Wissenschaft; Forschung; Übergangswirtschaft; Institutioneller Wandel; Osteuropa